Orexin-A Suppresses Signal Transmission to Dopaminergic Amacrine Cells From Outer and Inner Retinal Photoreceptors - Qiao, Sheng-Nan (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: The neuropeptides orexin-A and orexin-B are widely expressed in the vertebrate retina; however, their role in visual function is unclear. This study investigates whether and how orexins modulate signal transmission to dopaminergic amacrine cells (DACs) from both outer retinal photoreceptors (rods and cones) and inner retinal photoreceptors (melanopsin-expressing intrinsically photosensitive retinal ganglion cells [ipRGCs]). METHODS: A whole-cell voltage-clamp technique was used to record light-induced responses from genetically labeled DACs in flat-mount mouse retinas. Rod and cone signaling to DACs was confirmed pharmacologically (in wild-type retinas), whereas retrograde melanopsin signaling to DACs was isolated either pharmacologically (in wild-type retinas) or by genetic deletion of rod and cone function (in transgenic mice). RESULTS: Orexin-A attenuated rod/cone-mediated light responses in the majority of DACs and inhibited all DACs that exhibited melanopsin-based light responses, suggesting that exogenous orexin suppresses signal transmission from rods, cones, and ipRGCs to DACs. In addition, orexin receptor 1 antagonist SB334867 and orexin receptor 2 antagonist TCS OX229 enhanced melanopsin-based DAC responses, indicating that endogenous orexins inhibit signal transmission from ipRGCs to DACs. We further found that orexin-A inhibits melanopsin-based DAC responses via orexin receptors on DACs, whereas orexin-A may modulate signal transmission from rods and cones to DACs through activation of orexin receptors on DACs and their upstream neurons. CONCLUSIONS: Our results suggest that orexins could influence visual function via the dopaminergic system in the mammalian retina.